Interrelationship Among Rice Grain Arsenic, Micronutrients Content and Grain Quality Attributes: An Investigation From Genotype × Environment Perspective - Moulick, Debojyoti; Ghosh, Dibakar; Skalicky, Milan; Gharde, Yogita; Mazumder, Muhammed Khairujjaman; Choudhury, Shuvasish; Biswas, Jayanta Kumar; Santra, Subhas Chandra; Brestic, Marian; Vachova, Pavla; Hossain, Akbar (Frontiers in Environmental Science, 2022)
Arsenic contamination in the rice agro-ecosystem, its consequent spread into the food chain, and its adverse impact are a global concern. However, assessment of the impact of arsenic contamination on the qualitative aspect of rice in the post-harvest phase has not been attempted. We laid down this particular experiment with the aim to assess how arsenic contamination influences the grain quality attributes and other elemental profiles of four popular rice varieties. The entire field study was conducted in the lower Indo-Gangetic plain from genotype (four) and environment (14 locations) interaction point of view, using the additive main effects and multiplicative interaction model. Our findings indicate that grain arsenic content can influence the grain quality attributes and other elemental profiles in a low to highly significant manner. Amylose content (r = 0.753), cooking time (r = 0.706), and gruel solid loss (r = 0.672, 0.721) were found to be positively correlated with grain arsenic content in high-yielding varieties. Noteworthy variations in micronutrient content like iron (6.63–9.23 mg kg−1), zinc (3.15–5.54 mg kg−1), and copper (2.04–3.86 mg kg−1) as well as soil properties are also visible. Moreover, indigenous rice varieties respond differently than high-yielding varieties. Besides these, a pronounced impact of gene/variety and environment interaction can be seen. The findings clearly indicate that the qualitative aspect of rice is also prone to As contamination. These outcomes will attract the attention of policy-makers and researchers to develop rice varieties that have desirable quality attributes appropriate for the arsenic-contaminated regions of the world for sustainable rice production.